Information Quality of Regional Government’s Websites in Central Java Province - Ratnasari, Eny; Afrilia, Ascharisa Mettasatya; Putri, Wahyu Eka (Mediator: Jurnal Komunikasi, 2023)
As stated in the Public Information Disclosure Act, Government Public Relations bears a dual responsibility, managing both the main website of the regional government and the PPID (Information and Documentation Management Official) websites. This research analyzes the content of the PPID websites of 29 districts and 6 cities in Central Java Province. This research used a website assessment instrument consisting of 84 questions. This instrument is a modification of the Industrial Website Evaluation Model which focuses on information quality and information disclosure policies in Indonesia. The research results indicate that the implementation of the public information disclosure policy has not yet fully aligned with government public relations ethics. Several aspects still require improvement. Government Public Relations needs to focus on empathy in managing the PPID website and needs to acknowledge the behavior of the public who tend to access the main website belonging to each institution, not the PPID website. Therefore, government public relations needs to distinguish between the content of the main website and the PPID website. However, commitment is required in managing the PPID website to ensure that people are motivated to access information and can do so effectively.